Fatigue failure analysis using the theory of critical distance - Ruslizam, Daud; Ahmad Kamal, Ariffin; Shahrum, Abdullah; A. Emran, Ismail (Malaysian Association for Computational Mechanics (MACM) and Far East and Oceanic Fracture Society (FEOFS), 2011)
This conference was jointly organised by the Malaysian Association for Computational Mechanics (MACM), the Far East and Oceanic Fracture Society (FEOFS), the Malaysian Tribology Society (MyTribos) and the Malaysian Structural Integrity Research Group (MSI) from 7th - 9th June 2010 at Kuala Lumpur, Malaysia.